2021
DOI: 10.3390/jpm11090879
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Takotsubo Syndrome as A Bridge to Personalized Treatment

Abstract: Takotsubo syndrome (TTS) consists of transient dysfunction of the left and/or right ventricle in the absence of ruptured plaque; thrombus or vessel dissection. TTS may be divided into two categories. Primary TTS occurs when the cause of hospitalization is the symptoms resulting from damage to the myocardium usually preceded by emotional stress. Secondary TTS occurs in patients hospitalized for other medical; surgical; anesthetic; obstetric or psychiatric conditions who have activation of their sympathetic nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(67 reference statements)
0
2
0
1
Order By: Relevance
“…Primary cases are admitted to the hospital due to symptoms related to heart disease. On the other hand, secondary TTS cases are admitted to the hospital due to other disease and these patients develop TTS within the hospital stay [ 27 ]. Data have shown that both categories are associated with different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cases are admitted to the hospital due to symptoms related to heart disease. On the other hand, secondary TTS cases are admitted to the hospital due to other disease and these patients develop TTS within the hospital stay [ 27 ]. Data have shown that both categories are associated with different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, en un tercer momento se demuestra FA con respuesta ventricular alta pudiendo ser un evento incidental, ya que la paciente reunió condiciones para desarrollarla; formar parte del síndrome cerebro-corazón; ser secundaria al infarto de miocardio 18 o tratarse de FA preexistente, las cuales se detectan con mayor frecuencia después de un ACV; esto genera un debate para demostrar que los episodios de FA se desencadenan por el síndrome cerebro-corazón o son la causa del ictus inicial 1 , 2 . Estos tres eventos (ACV isquémico, síndrome de Takotsubo y FA) forman parte del síndrome cerebro-corazón que ocurre con mayor frecuencia dentro de los primeros tres días del evento cerebrovascular, estando asociado a la edad avanzada, prevalencia de comorbilidades cardíacas y factores de riesgo cardiovascular 1 , 2 , lo cual explica el daño cardíaco por la interacción a través del eje nerviosos cerebro-corazón causando inflamación, desregulación autónoma central, liberación de catecolaminas, cambios estructurales del miocardio y anomalías de la pared vascular 2 , 19 .…”
Section: Discussionunclassified
“…Moreover, high levels of circulating catecholamines reduce receptivity to vasodilatory mediators. This may be the cause of a sudden drop in flow-mediated vasodilatation at admission, whereas a gradual drop in catecholamine levels in the blood may result in an increase in flow-mediated vasodilatation values at discharge [ 33 ]. Furthermore, different grades of perfusion (TIMI) have been observed in angiographic studies [ 34 ].…”
Section: Pathophysiology Of Ttsmentioning
confidence: 99%